THE ROLE OF LIBERAL-LEGAL THINKING IN THE LATE 19TH AND EARLY 20TH CENTURIES IN CONTEMPORARY JUDICIAL EDUCATION - Puzikov, Ruslan; Makarova, Olga (Administrative and Criminal Justice, 2015)
The article analyzes the role and place of the liberal-legal thinking in the late 19th and early 20th centuries in contemporary judicial education. The authors point out that many of the ideas of liberal scholars of this period are relevant nowadays, but they are not covered by the training course in law schools.